Optimalisasi Penerapan Hygiene Sanitasi Dan 5s Di Desa Wangun Jaya Kecamatan Cikalong Wetan Kabupaten Bandung Barat - Asep Kurniawan; Eka Ludiya; Yun Yun; Lukman Hakim Munawar Fauzi (Universitas Lancang Kuning, 2023)
In the era of Covid19 health is something that must be considered, because one of the causes of disruption to one's health comes from food. Likewise with MSMEs located in Wangun Jaya Village, Cikalong Wetan District, West Bandung Regency, which have the potential to develop their business in the food and beverage sector, but in reality they often neglect doing basic things such as washing hands, washing raw materials and providing tools. clean cook to use. It can be seen that there is still a lack of awareness of health, so it is very important to understand sanitation hygiene and manage work areas through the 5S approach (Seiri, Seiton, Seiso, Seiketssu, and Shitsuke) from business actors. The results show that SMEs are able to understand and apply sanitary hygiene and 5S in running their business. And it is hoped that there will be changes in behavior in terms of hygiene, health and safety at work.